Pull motivation and well-being as drivers of entrepreneurial success: The moderating role of social capital - Shibo Li; Edwin Setiawan Sanusi (PLoS ONE, 2025)
This study examines the interplay between entrepreneurial motivation, mental well-being (MWB), and business performance, with a focus on the moderating role of bridging social capital among female entrepreneurs in China. Drawing on Conservation of Resources (COR) and Social Capital theories, the research highlights the critical role of pull motivation in fostering MWB, which subsequently enhances business performance. The findings, based on moderated mediation analysis, reveal that MWB mediates the relationship between pull motivation and business performance, and this mediation effect is amplified in contexts with higher levels of bridging social capital. The study makes several contributions. Theoretically, it extends COR theory by illustrating how resource gain spirals initiated by intrinsic motivation led to psychological and business success. It also enriches Social Capital theory by demonstrating how expansive social networks facilitate entrepreneurial outcomes. Practically, the findings underscore the importance of fostering intrinsic motivation and building diverse social networks to support female entrepreneurs. The results hold implications for policymakers and practitioners aiming to enhance women’s entrepreneurial well-being and performance, particularly in socio-cultural contexts that impose unique challenges. Despite its contributions, the study has limitations. The cross-sectional design restricts causal inference, and the findings are contextualized within the Chinese entrepreneurial ecosystem, which may limit generalizability. Future research should explore longitudinal designs and expand the scope to other cultural and economic settings. By addressing these areas, scholars can further unravel the complex dynamics of motivation, well-being, and social capital in entrepreneurship.